PENGAWASAN IZIN PENJUALAN MINUMAN BERALKOHOL DI TEMPAT HIBURAN KOTA PEKANBARU - Cynthya Mesdiyana Cynthya Mesdiyana; Abdul Sadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Alcoholic drink are drinks contain ethanol produce from distillation which is produceby fermentation of grains, fruits and vegetables. The Government of Pekanbaru through the Department of Trade and Industry continues to strive to supervise the licenses for the sale of alcoholic beverages in Pekanbaru  Entertainment Venues. These efforts are state in Minister of Trade Regulation Number 20/M-DAG/PER/4/2014 concerning Control and Supervision of the Procurement, Distribution and Sales of Alcoholic Beverages. The theoretical concept used is Supervision according to Stoner, dkk., claims that the supervision process consists of four variables, namely Determination of Standards and Performance Assessment Methods, Performance Evaluation, Comparing Performance with Standards, and Taking Corrective Action. The purpose of this study is to find out how the supervision and what factors affect the Supervision of Alcoholic Beverage Sales Permit in Pekanbaru Entertainment Venues. This research used a qualitative method with descriptive data review. In collecting the data the researchers used interview, observation and documentation techniques using purposive sampling techniques as a source of information and data analysis with qualitative descriptive methods. The results of the study showed that the Supervision of Licensing on the sale of alcoholic beverages in Pekanbaru  Entertainment Venues has been carried out even though it is still not effective because lack of Humen Resources, disobedience of owners of entertainment venues to the rules and lack of coordination between agencies. Keywords: Supervision, Permission, Alcoholic Beverages